2005
DOI: 10.1080/17402520500182295
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Regulation of Local Immune Responses Resulting in Atherosclerosis

Abstract: Atherosclerosis is nowadays generally accepted as an inflammatory disease but the mechanism of its origin and development have not yet been fully clarified. The present review focuses on the role of the local immune system as one of the key players in the pathogenesis of the complex process. Its part represented by vascular-associated lymphoid tissue (VALT) within the arterial wall participates directly in the vascular wall's homeostatis. Its inordinate activation during ontogenic development of an individual,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…They appear in the arterial intima as early as in 1-year-old children in lesions called "fatty streaks" [8]. Cytotoxic CD8+ T cells also take present in atheromatous lesions, but are less abundant [8].…”
Section: The Involvement Of Cellular Immunitymentioning
confidence: 98%
See 3 more Smart Citations
“…They appear in the arterial intima as early as in 1-year-old children in lesions called "fatty streaks" [8]. Cytotoxic CD8+ T cells also take present in atheromatous lesions, but are less abundant [8].…”
Section: The Involvement Of Cellular Immunitymentioning
confidence: 98%
“…Immunohistologic observations revealed that the primary cells to appear in the arterial intima in future atherosclerosis sites are lymphoid cells [8]. T cells are abundant in the atherosclerotic plaques, and TH1 lymphocytes with their pro-inflammatory cytokines (TNF-α, IFN-γ, IL-2) dominating over TH2 lymphocytes, releasing anti-inflammatory mediators such as IL-4, IL-5, and IL-10 [8].…”
Section: The Involvement Of Cellular Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the described features are linked to an autoimmune response remains to be elucidated (36,37). In this respect, the increase CD4/CD8 ratio may resemble the ratio of other autoimmune disorders such as multiple sclerosis (38).…”
Section: Discussionmentioning
confidence: 99%